The genus Drepanura (Collembola: Entomobryidae) in Australia: descriptions of two new species and redescriptions of five known species - Ma, Yitong; Chun, Zhao; Greenslade, Penelope (Zootaxa, 2015)
Seven Australian species of the genus Drepanura are reported. Two of the seven are new and five are redescribed. The new species are: D. liuae sp. nov. and D. polychaeta sp. nov. Redescriptions are given for D. albocoerulea (Schött, 1917), D. cinquilineata Womersley, 1934, D. citricola Womersley, 1934, D. cobaltina (Schött, 1917) and D. coeruleopicta (Schött, 1917). The chaetotaxy is described and a key to the Australian species of the genus is given.